Patterns and correlates of expressed emotion, perceived criticism, and rearing style in first admitted early-onset schizophrenia spectrum disorders - Polier, Georg von; Resch, Franz; Koch, Eginhard (The journal of nervous and mental disease, 2014)
The aim of this study was to assess patterns and correlates of family variables in 31 adolescents treated for their first episode of a schizophrenia spectrum disorder (early-onset schizophrenia [EOS]). Expressed emotion, perceived criticism, and rearing style were assessed. Potential correlates were patient psychopathology, premorbid adjustment, illness duration, quality of life (QoL), sociodemographic variables, patient and caregiver “illness concept,” and caregiver personality traits and support. Families were rated as critical more frequently by patients than raters (55% vs. 13%). Perceived criticism was associated with worse QoL in relationship with parents and peers. An adverse rearing style was associated with a negative illness concept in patients, particularly with less trust in their physician. Future research should examine perceived criticism as a predictor of relapse and indicator of adolescents with EOS who need extended support and treatment. Rearing style should be carefully observed because of its link with patients’ illness concept and, potentially, to service engagement and medication adherence.
Gesehen am 22.09.2020